A historical perspective of MDR invasive pneumococcal disease in Spanish adults. (30th November 2020) - Càmara, Jordi; Grau, Inmaculada; González-Díaz, Aida; Tubau, Fe; Calatayud, Laura; Cubero, Meritxell; Domínguez, M Ángeles; Liñares, Josefina; Yuste, José; Pallarés, Román; Ardanuy, Carmen
Abstract: Objectives: To analyse the clonal dynamics and clinical characteristics of adult invasive pneumococcal disease (IPD) caused by MDR and penicillin-non-susceptible (PNS) pneumococci in Spain. Methods: All adult IPD episodes were prospectively collected (1994–2018). Streptococcus pneumoniae isolates were serotyped, genotyped and tested for antimicrobial susceptibility. Changes in the incidence of IPD were analysed and risk factors contributing to MDR were assessed by logistic regression. Results: Of 2095 IPD episodes, 635 (30.3%) were caused by MDR/PNS isolates. Over the study period, the incidence of MDR/PNS-IPD decreased (IRR 0.70; 95% CI 0.53–0.93) whereas that of susceptible isolates remained stable (IRR 0.96; 95% CI 0.80–1.16). A reduction of resistance rates to penicillin (–19.5%; 95% CI –37% to 2%) and cefotaxime (–44.5%; 95% CI –64% to –15%) was observed. Two clones, Spain 9V -ST156 and Denmark 14 -ST230, accounted for 50% of current resistant disease. Among current MDR/PNS isolates, 45.8% expressed serotypes not covered by the upcoming PCV15/PCV20 vaccines. MDR/PNS episodes were associated with older patients with comorbidities, nosocomial acquisition and higher 30 day mortality. MDR/PNS pneumococci were not independently associated with 30 day mortality in multivariate analysis [OR 0.826 (0.648–1.054)]. Conclusions: Our study shows an overall reduction of MDR/PNS isolates in adults after the introduction of pneumococcal conjugate vaccines. However, a significant proportion of current resistant isolates are not covered by any of the upcoming PCV15/PCV20 vaccines. The burden of resistant disease is related to older patients with underlying conditions and caused by two major clones. Our data show that MDR is not a statistically significant factor related to increased mortality.